The Implementation of Merdeka Curriculum Towards Early Childhood Education - Hariyani, Indaria Tri; Sulistiyani , Sulistiyani; Soemarmi , Soemarmi; RZ, Fida (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The issues faced by early childhood education or PAUD dealing with the implementation of the Merdeka curriculum is the teachers’ readiness in implementing the Merdeka curriculum. The purpose of this research is to assist PAUD teachers in preparing for the implementation of the Merdeka curriculum. The research method used in this study was qualitative descriptive, that is, concerning the real condition of six teachers at one PAUD school in Surabaya. The data were gathered by using interviews and observations of the head of school, curriculum representatives, and all teachers for guidelines for interviews that have been validated by three validators. The data analysis was done using an interactive model by Miles and Huberman, which consists of four stages: data collection, data reduction, data presentation, and conclusion. The results of this study showed that the Merdeka curriculum has already been implemented in PAUD, but it requires some improvement and development since the Merdeka curriculum only begins the first year at PAUD. Therefore, there is little research on the implementation of the Merdeka curriculum, so it is recommended to undertake further in-depth research into the application of the Merdeka curriculum at the next level of school.